Application of Contrast‐Enhanced Ultrasound in the Differential Diagnosis of Benign and Malignant Subpleural Pulmonary Lesions. (13th August 2021) - Shen, MengJun; Bi, Ke; Cong, Yang; Chen, HongWei; Zhang, Yi; Zhu, HuiMing; Wang, Yin
Abstract : Objective: To explore the clinical value of contrast‐enhanced ultrasound (CEUS) in the differential diagnosis of benign and malignant subpleural pulmonary lesions (SPLs). Methods: Among 959 patients with SPLs who were scheduled to undergo ultrasound‐guided puncture in our department between January 2019 and June 2019, 506 patients were included and their B‐mode ultrasound and CEUS features, including the lesion's location, size, margin, echo, perfusion pattern of ultrasound contrast agent, degree of enhancement, homogeneity, vascular signs, and necrosis, were retrospectively investigated. All malignant cases were diagnosed by pathology, while benign cases were diagnosed by two respiratory physicians after comprehensive analysis of pathology, etiology, imaging, and clinical symptoms. Statistical differences in these features between the benign and malignant groups were then analyzed. Results: There were 506 cases in this study, including 219 benign cases and 287 malignant cases. Among them, 351 were males and 155 were females, with an average age of 59 ± 16 years. There were statistically significant differences between benign and malignant groups in the perfusion pattern, the degree of enhancement, and vascular signs. The features of the malignant group included local‐to‐whole perfusion pattern, hypo‐enhancement, and curly hair sign, while those of the benign group included a centrifugal perfusion pattern, iso‐enhancement and hyper‐enhancement, and dendritic sign. There was no statistically significant difference between the two groups in homogeneity and necrosis. Conclusions: CEUS enhancement mode is different between benign and malignant SPLs, which can provide supplementary information for the differential diagnosis of SPLs in the existing imaging diagnosis.